INFLUENCER STRATEGI MARKETING EFEKTIF UNTUK MEMPROMOSIKAN PARIWISATA KABUPATEN BULELENG - Ida Ayu Devi Arini (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
The purpose of this research is to provide an alternative pattern of promotion by using influencers to help promote tourism in Buleleng district, especially by attracting the millennial generation. The existence of influencers is very influential in determining travel decisions, because influencers are public figures who have many followers. This research is a qualitative descriptive study. The primary data in this study was sourced from observations on social media influencers and from interviews, while the secondary data came from scientific journals and books that assisted in this research. The collected data is then selected to assist the analysis and the last step is drawing conclusions. The results of this study become a recommendation for the local government of Buleleng Regency to try to use tourism promotion with influencer services.Keywords: Influencer, Marketing, Tourism